Pemberdayaan Pelaku UMKM dan Ibu-Ibu PKK dalam Semangat Gotong Royong untuk Menunjang Penguatan Ekonomi di Dusun Gaten, Kalurahan Sumberrejo - Muhammad Safrudin; Beni Winawan; Farhan Arif Pradana; Assyifa Fiqria Salamah; Desta Sekar Riswandari; Herlambang Nugroho; Rafianti M Djumadil; Rio Susila (Lembaga Pengembangan Kinerja Dosen, 2025)
Gaten Hamlet, Sumberrejo Village, holds significant local economic potential through the Micro, Small, and Medium Enterprises (MSMEs) initiative and the active participation of Family Welfare Empowerment (PKK) mothers. This study aims to analyze in depth effective empowerment strategies in supporting economic strengthening in Gaten Hamlet, by integrating and prioritizing the value of mutual cooperation as the main pillar. Using a descriptive qualitative approach, data were collected through in-depth interviews with MSME actors, PKK members and administrators, and community leaders, complemented by participatory observation and implementation of training. The results of the study indicate that the synergy of capacity building training programs, facilitation of access to capital and marketing, and strengthening community networks based on mutual cooperation have been proven to significantly increase MSME productivity and family economic independence. Mutual cooperation not only functions as a social glue, but also becomes a driving force for collaboration in various stages, from production, distribution, to promotion of local products. The implications of this study highlight the importance of developing policies that support community-based economic ecosystems and the sustainability of empowerment programs through active participation and community ownership.